Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Keywords: Official Language Minority Community (OLMC)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

The South Shore of Montérégie-Centre : Towards a Portrait of the English-speaking Community - Assistance and Referral Centre (ARC); Richardson, Mary (2019)

Promoting Opportunities for Youth Community Partnerships : A Policy Brief - Lai, Edward; Winrow, Adrienne; Orme, Charlie (Youth for Youth Québec (Y4Y Québec), 2019)
Across Canada, youth retention and success have always been key in ensuring the continued vitality of official language minority communities (OLMCs). Within the context of Quebec, retention in particular is a constant challenge, where English-speaking youth are disproportionately apt to pursue professional opportunities outside of the province. While this option should never be condemned, it is nonetheless important to ensure that those who wish to remain have access to the resources necessary to help them thrive therein. With this in mind, and considering that youth retention is equally beneficial to the state, policymakers need to be in a position to support organizations that are working towards this objective.
Keywords: Official Language Minority Community (OLMC)

Careers in Mental Health - Assistance and Referral Centre (ARC) (2019)

Careers in Nursing - Assistance and Referral Centre (ARC) (2019)

Technical Medical Careers - Assistance and Referral Centre (ARC) (2019)

Therapy & Rehabilitation Careers - Assistance and Referral Centre (ARC) (2019)